Cardioneuroablation for Drug Refractory Vasovagal Syncope After COVID-19 Infection - Stefanos Zafeiropoulos, MD, PhD; Nicholas J. Beccarino, MD; Stavros Stavrakis, MD, PhD; Stavros Zanos, MD, PhD; Raman Mitra, MD, PhD (JACC: Case Reports, 2024)
Cardioneuroablation is a novel approach to treat patients with recurrent vasovagal syncope (VVS), targeting the ganglionated plexi around the atria and thus reducing the vagal input to the heart. This study reports a case of drug-refractory VVS after COVID-19 infection, successfully managed with cardioneuroablation.